DETERMINAN ADOPSI DIGITAL BANKING DI KALANGAN MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DIPONEGORO: PENDEKATAN REGRESI LOGISTIK - Indah Susilowati; Yeremia Petra; Talenta Vena Insani; Tegar Hermawan; Yasmien Mumtaz Azzahra; Penesta Tia Tira Sinulingga (Universitas Nias Raya, 2025)
The development of digital technology has driven a major transformation in the banking sector, enabling various services to be provided online through digital banking platforms. Students, as the digital native generation, are an important segment in the adoption of these services. Although various conveniences and benefits have been offered, the level of digital banking adoption among students remains uneven. This study aims to examine the interest of students from the Faculty of Social and Political Sciences (FISIP) in using digital banking and to explore the factors influencing their preferences. This research employs a quantitative approach using logistic regression analysis. Primary data were collected through questionnaires distributed to active FISIP students at Diponegoro University. Independent variables include age, GPA, semester, region of origin, entrepreneurial status, monthly allowance, and ICT literacy, with digital banking adoption as the dependent variable. The results indicate that the logistic regression model has a satisfactory goodness-of-fit, with a -2 Log Likelihood value of 99.003 and a Nagelkerke R² of 0.154. Hypothesis testing revealed that only age and semester significantly influence digital banking adoption. Age has a positive effect (p = 0.003), while semester has a negative effect (p = 0.005). Other variables—GPA, region of origin, side business, monthly allowance, and ICT literacy—show no significant effect. This study contributes conceptually to understanding technology adoption behavior and offers practical implications for financial institutions and educational bodies to enhance financial literacy and digital inclusion among students.